Modification of surfactant chemical structure for optimising graphene oxide systhesis as an efficient removal of methylene blue - Nur Amirah Jamaluddin (Tanjong Malim, 2023)
Modification of surfactant chemical structure for optimising graphene oxide systhesis as an efficient removal of methylene blue by Nur Amirah Jamaluddin